1976
DOI: 10.1002/j.2050-0416.1975.tb06962.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mycoflora of Malt

Abstract: The mycoflora of malt which caused gushing beer has been investigated and compared with the mycoflora of malt from nine malting plants in Sweden, Denmark, Finland and England. Malt which caused gushing beer was found to contain a high proportion of grains contaminated by Aspergillus, Penicillium and Rhizopus. The commonest species isolated were found to be Aspergiffus fumigatus and Aspergillus amstelodami. These fungi occurred on all malt samples investigated independent of their origin. The mycoflora on malt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
1
7
1
1
Order By: Relevance
“…(1965) found experimental evidence that Fusarium species had an adverse effect on malt quality, and caused gushing in beer produced from infected malt. Results were confirmed by various other authors (Gylang and Martinson 1976; Haikara 1980; Weideneder 1992; Niessen et al. 1992; Zepf 1998).…”
Section: Introductionsupporting
confidence: 82%
“…(1965) found experimental evidence that Fusarium species had an adverse effect on malt quality, and caused gushing in beer produced from infected malt. Results were confirmed by various other authors (Gylang and Martinson 1976; Haikara 1980; Weideneder 1992; Niessen et al. 1992; Zepf 1998).…”
Section: Introductionsupporting
confidence: 82%
“…The range of filamentous fungi recovered in this study is in line with previous observations of the mycoflora of plant organs and barley malt. Thus, representatives of the genera Alternaria, Aspergillus, Cladosporium, Fusarium, Mucor, Penicillium and Phoma have been recovered from healthy leaves of a wide variety of plant species (Lamb & Brown 1970;Ruscoe 1971 ;Bewley 1979) and barley malt (Gyllang & Martinson 1976;Flannigan et al 1982). Consistently, Alternaria alternata has been regarded as the most common field fungus on malting barley and as being a prominent species during malting ( e g Haikara et at.…”
Section: Discussionmentioning
confidence: 99%
“…Numbers of some moulds, such as Aureobasidium pullulans, Geotrichum candidum and Fusarium spp., may increase during germination (Flannigan el al., 1984) and then decline with kilning, but others such as Rhizopus spp. and Aspergillus fumigatus have been found to spread during kilning (Gyllang & Martinson 1976).…”
mentioning
confidence: 99%
“…. V důsledku pokračujícího úsilí o vyjasnění příčin gushingu se objevilo, že přepěňování úzce souvisí s napadením ječ-mene plísněmi a jejich modifikacemi během skladování a sladování (Gjertsen et al ., 1965;Amaha et al ., 1973;Gyllang a Martinson, 1976;Haikara, 1980;Weideneder, 1992;Niessen, 1993;Zepf, 1998) .…”
Section: Historie a Nové Trendy V Oblasti Výzkumu Přepěňování Pivaunclassified
“…. An ongoing effort to clarify the causes of gushing revealed that over-foaming is closely connected with infection of barley with fungi and their modification during storage and malting (Gjertsen et al ., 1965;Amaha et al ., 1973;Gyllang and Martinson, 1976;Haikara, 1980;Weideneder, 1992;Niessen, 1993;Zepf, 1998) .…”
Section: Historie a Nové Trendy V Oblasti Výzkumu Přepěňování Pivamentioning
confidence: 99%